The Effect of Information Services Toward Confidence Students’ in Expressing Opinions - Dina Hidayati Hutasuhut; Muhammad Noer Fadlan (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2021)
This research aims to determine the effect of information services on confidence in expressing opinions in student online lectures. The method used in this study is a quantitative method. This type of research is a quasi-experimental with the type of Pre test-post test one group design. The subjects in this study were 30 students in semesters 1 and 3 who had low confidence in expressing their opinions. The instrument used is a self-confidence scale in expressing opinions. Instruments are given before and after the implementation of information services. Data were analyzed using the Wilcoxon test. Pre-test data in the experimental group obtained an average = 73.5 while the post-test data obtained an average = 119.30. This data is in accordance with the Wilcoxon level test obtained Jcount = 132 while Jtable = 105. Based on the critical value table J for the Wilcoxon marked level test for n = 30, = 0.05 the hypothesis is accepted. That is, there is a significant effect of providing information services on confidence in expressing opinions on online student recovery.